ENHANCING ENGLISH VOCABULARY ACQUISITION IN GRADE 1 STUDENTS: A COMPARISON OF SONG-BASED AND STORYTELLING LEARNING STRATEGIES. - Rufaidah, Iffah; Rahmi, Tuti (Universitas Muhammadiyah Makassar, 2025)
In Indonesia, formal foreign language learning typically begins in school. Among the various challenges that students often encounter, vocabulary acquisition is a significant one. An adequate vocabulary base is crucial as it enables learners to effectively comprehend linguistic input (through listening and reading) and to produce coherent output (in speaking and writing). Therefore, this study investigated the effectiveness of song-based and storytelling-based learning methods on English vocabulary acquisition among first-grade elementary school students. A quasi-experimental pretest-posttest control group design was employed with 30 participants, divided into three groups: a song-based learning group (n=10), a storytelling-based learning group (n=10), and a control group (n=10) that received no specific intervention. Results indicated that the song-based learning group achieved the highest mean gain score in vocabulary acquisition (61.2), compared to the storytelling-based learning group (45.0) and the control group (20.0). Statistical analyses confirmed significant differences in vocabulary acquisition gain scores among the groups. Post-hoc tests revealed that both intervention groups performed significantly better than the control group. Although the song-based learning group showed a descriptively higher mean gain score than the storytelling group, this difference was not statistically significant. These findings suggest that incorporating songs can effectively enhance engagement and retention in early English language learning.